The Implementation Of 3S (SDKI, SIKI, SLKI) to The Quality Of Nursing Care Documentation In Hospital’s Inpatient Rooms - Wiwin Sulistyawati; Susmiati Susmiati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The implementation of 3S (SDKI, SIKI, and SLKI) is a benchmark used as a guideline for the enforcement of nursing diagnosis, nursing intervention, and a nursing outsider to provide safe, effective, and ethical nursing care. This study aims to analyze the implementation of 3S on the quality of documentation in hospital inpatient rooms. Research design correlation analysis with the cross-sectional approach. The research sample of implementing nurses in hospital inpatient rooms who have implemented 3S. Sampling techniques use sampling quotas. Based on Chi-Square test results obtained, p-value = 0.001 < α 0.005 . It means there is a relationship of application of 3S to the quality of nursing care documentation in hospital inpatient rooms. Based on the results of this study, the Head of Nursing is expected to implement 3S to improve the quality of nursing care documentation, which will have an impact on improving the quality of nursing services